Clinical outcomes after 24 months of insulin therapy in patients with type 2 diabetes in five countries: results from the TREAT study. (17th June 2013) - Oguz, A.; Benroubi, M.; Brismar, K.; Melo, P.; Morar, C.; Cleall, S.P.; Giaconia, J.; Schmitt, H.
Abstract: Objective: To assess factors associated with insulin regimens at initiation, changes in treatment and metabolic control over 2 years of insulin therapy in patients with type 2 diabetes in five countries. Research design and methods: TREAT was a prospective, 24 month, observational study in patients with type 2 diabetes initiating insulin in clinical practice. Patient characteristics were collected at baseline and metabolic outcomes at 3, 6, 12, 18 and 24 months after initiation. Results: A total of 985 patients were enrolled, 886 assessed at baseline and 734 (82.8%) at 24 months. Baseline characteristics varied between countries: 52.8% of patients were men; mean age was 60.4 years; body mass index, 29.7 kg/m 2 ; time since diagnosis, 10.1 years; HbA1c, 9.6%. Less than 25% of patients met ADA/IDF targets for blood pressure/LDL cholesterol. Overall, 50.1% of patients were initiated on long/intermediate insulin, 39.3% on mixture and 7.8% on basal–bolus; distribution varied between countries. Patients on long/intermediate were more likely to have lower baseline HbA1c and be intensified to other regimens (19.4%). No oral antidiabetic medication was used for 16.4% initiating on long/intermediate, 47.4% on mixture and 62.3% with basal–bolus. Overall, mean HbA1c decreased from 9.6% to 7.6%, with little difference between regimens at endpoint. The percentage of patients with hypoglycaemia was highest at 6 months and with basal–bolus. Limitations: Sites were not selected at random. Drop-out of patients prior to 24 months may have introduced a bias that favoured responders. Conclusions: Mean baseline HbA1c was high, indicating delayed initiation of insulin treatment. Blood pressure and lipids were suboptimally controlled. Insulin regimens varied between countries, changed little and resulted in similar HbA1c levels after 24 months.